Microbiology of the food chain. Horizontal method for detection and enumeration of Campylobacter spp. Detection method. Inclusion of methods for molecular confirmation and identification of thermotolerant Campylobacter spp, the use of growth supplement in Preston broth and changes in the performance testing of culture media Part 1, (20th February 2023) - British Standards Institution
No abstract available